OVERVIEW OF DYSMENORRHEA SEVERITY AND MANAGEMENT CHOICES AMONG FEMALE MEDICAL STUDENTS AT UNIVERSITAS MULAWARMAN: THE 2024 COHORT - Kalya Natriswa Putri Kinanthi; Khairunnida Rahma (Mulawarman International Conference on Tropical Public Health, 2025)
Dysmenorrhea is a highly prevalent gynecological complaint that significantly interferes with daily activities. This study aimed to investigate the severity levels of dysmenorrhea and treatment preferences among female medical students from the 2024 cohort at Universitas Mulawarman. A descriptive quantitative design was employed using a questionnaire administered to 50 respondents, with data analyzed through frequency distribution and percentage methods. The results showed that most respondents experienced non-severe dysmenorrhea, with mild pain reported by 46% and moderate pain by 42% of participants; however, dysmenorrhea still disrupted daily activities in 64% of the students. Regarding management strategies, the majority preferred non-pharmacological approaches, particularly relaxation techniques (36%) and drinking mineral water (20%). In conclusion, although dysmenorrhea among the students was generally mild to moderate, management preferences predominantly favored simple, non-pharmacological interventions.